Lexique courant, familier, populaire, vulgaire, argotique du français : correlation notionnelle et terminologique - Mokraya, О. (Культура народов Причерноморья, 2013)
The French words relating to everyday, colloquial, popular, vulgar and argo: notional and terminological correlations The language is one of the elements of the culture. Cités, which are mainly located in the suburbs of the major cities of France are often theater production of specific cultural norms. This language is called familiar, domestic, popular, vulgar, slang. It is good to mark that language and vocabulary, in particular, arise from the same natural sources, that is to say French and Latin, provincial and foreign. A choice of vocabulary is realized, of course, depending on the situation of communication. But there exists some ambiguity in identifying the words that make up spoken French. These lexemes are nominated as current (courants), conversational (familiers), folk (populaires), vulgar (vulgaires), argo (argotiques). The paper interprets of the terms: vocabulary, conversational vocabulary, everyday language, slang, taking into consideration the development of linguistic research in the field of French lexicology. Clarifying this problematic issue to students of higher educational establishments is up to date as vocabulary competence is always relevant for would-be linguists. However, it is necessary to know how to identify these words for linguistic research students who are keenly interested in the study of language of young French. This is based on the language of the suburb city and is a mixture of slang, words borrowed from French, slang old or different cultures that coexist in the city. Thus, clarify the status of colloquial language in contemporary French, define the place of familiar lexicon in the lexical system of contemporary French vocabulary, to differentiate the language of cities in France, different from standard vocabulary, will be the subject of study in this article. The structural and semantic peculiarities of the French lexicon constitute the scope of the search. Its purpose is, therefore, to define the linguistic properties of words belonging to the familiar register. Key words: conversational French, vocabulary, slang, vulgar vocabulary, argo.